ROLE OF MICRORNA IN PREDICTING OF ADENOCARCINOMA DEVELOPMENT IN BARRETT’S ESOPHAGUS - A. Z. Tsitskarava (Вестник хирургии имени И.И. Грекова, 2016)
Barrett’s esophagus is considered as a predictor of esophageal adenocarcinoma with multistage neoplastic progression at present time. The research assessed an expression of microRNA-21 in 25 patients with different degree of metaplasia and dysplasia of mucous coat of esophagus. The level of expression of microRNA depended on the presence and degree of expression of neoplastic changes of mucous coat of esophagus. The expression rising of microRNA was noted in patients with columnar-celled metaplasia and intraepithelial neoplasia and in case of esophageal adenocarcinoma. The treatment strategy could be determined by the method of estimation of the level of microRNA expression in biopsy material from mucous coat of esophagus in patients with gastroesophageal reflux disease and using other criteria.